Analisis Kualitas Sumber Daya Manusia Pada Departemen Quality Control Di PT. Kiyokuni Technologies Indonesia - Susan Larasati; Uus MD Fadli; Laras Ratu Khalida (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
The aim of this research is to assess the quality of human resources in the Quality Control department at PT. Kiyokuni Technology Indonesia. Highly skilled and competent employees in a company will increase operational efficiency, raise the standard of goods produced, and increase client happiness. This research uses qualitative methodology to examine markers of human resource quality, including work understanding, knowledge, skills and work motivation. Participants in this research consisted of HRD personnel, managers, supervisors and employees of PT. Kiyokuni Technology Indonesia. Primary data was obtained through face-to-face interviews with participants, and secondary data was obtained from a thorough review of existing literature and documentation. The results of this research show the importance of managers and team leaders exercising control in improving variables that have an impact on the performance of the Quality Control team. Managers can create a work climate that encourages professional growth and allows team members to reach their maximum potential by implementing a comprehensive strategy that focuses on individual development. In this way, the company can effectively achieve and fulfill its goals.